Structural diversity of anthocyanins in fruits - Goulas, Vlasios; Vicente, Ariel Roberto; Manganaris, George A. (My University, 2012)
Anthocyanins are water-soluble pigments responsible for blue, purple and red color of many fruits such as berries, grapes, cherries, pomegranates, plums, apples, and some citrus and tropical fruits. Anthocyanins have ecological functions as attractants to pollinators and/or predators,predators, provide protection against excessive radiation, act as antimicrobials and most promptly they have high antioxidant potencycapacity. Chemically, anthocyanins belong to a parent class of molecules, the flavonoids, and are glycosiydes containing a sugar moiety and an aglycone unit (the anthocyanidin) which is derived from the flavylium ion. More than 635 different anthocyanins and 23 anthocyanidins by now have been already described. The structural differences among anthocyanins are related to the number of hydroxyl or methoxyl groups in the anthocyanidin skeleton, the position and the number of bonded sugar residues as well as by the aliphatic or aromatic carboxylates bonded to them. The distribution of the six most common anthocyanidins in fruits is: cyanidin 30%, delphinidin 22%, pelargonidin 18%, peonidin 7.5%, malvidin 7.5% and petunidin 5%. The conformation of anthocyanins has great impact in their color, stability, copigmentat co-pigmentation capacity and antioxidant properties. The most common glycoside derivatives are 3-monosides, 3-biosides, 3,5 and 3,7-diglucosides. The 3-glucosyl derivatives of the three non-methylated anthocyanidins (cyanidin, delphinidin, pelargononidin) are the most common in nature. The content and diversity of anthocyanins in fruits are affected by genetic factors, environmental conditions and agricultural practices. Harvest maturity, manipulation, storage conditions (temperature, humidity), postharvest treatments as well as processing can deeply affect the steady state content of anthocyanins in fruits. In the current chapter, the distribution of anthocyanins in fruits is also described. In addition, the effect of pre-and postharvest conditions and/or treatments on their accumulation and fate is analyzed. 2012 Nova Science Publishers, Inc. All rights reserved.
Keywords: Anthocyanins; Agriculture, Forestry, and Fisheries; Water-soluble pigments; Ecological functions; Fruits